Prognostic value of Charlson Comorbidity Index in the elderly with a cardioverter defibrillator implantation. (1st September 2020) - Poupin, Pierre; Bouleti, Claire; Degand, Bruno; Paccalin, Marc; Le Gal, François; Bureau, Marie-Laure; Alos, Benjamin; Roumegou, Pierre; Christiaens, Luc; Ingrand, Pierre; Garcia, Rodrigue
Abstract: Background: Elderly patients are often underrepresented in implantable cardioverter defibrillator (ICD) trials, and ICD implantation in patients ≥75 years consequently remains controversial. We aimed to evaluate mortality, appropriate ICD therapy rates and survival gain in an elderly population after risk stratification according to the Charlson Comorbidity Index (CCI). Methods: This monocentric retrospective study included elderly ICD patients ≥75 years. They were subdivided according to their CCI score into 3 categories (0–1, 2–3 or ≥4 points). Elderly patients were matched 1:2 with younger control ICD patients on gender, type of prevention (primary or secondary) and type of device (associated cardiac resynchronization therapy or not). Results: Between January 2009 and July 2017, 121 elderly patients (mean age 78 ± 3; 83% male) matched with 242 controls (mean age 66 ± 5) were included. At 5 year follow-up after ICD implantation, overall survival was 78%, 57%, and 29% ( P  = 0.002) in the elderly with a CCI score of 0-1, 2-3 and ≥4 respectively, and 72% in controls. There was no significant difference regarding ICD appropriate therapy between the 3 subgroups despite a trend towards lower rates of therapy in CCI ≥ 4 points patients (34.2%, 39.7% and 22.8% respectively; P  = 0.45). Median potential survival gain after an appropriate therapy was >5, 4.7 and 1.4 years, with a CCI score of 0-1, 2-3 and ≥4 respectively ( P  = 0.01). Conclusion: Elderly patients with CCI score ≥ 4 had the lowest survival after ICD implantation and little survival gain in case of appropriate defibrillator therapy. More than age alone, the burden of comorbidities assessed by the CCI could be helpful to better select elderly patients for ICD implantation. Highlights: 5-year survival rate was 29% in elderly with Charlson Comorbidity Index ≥ 4. Elderly with Charlson Comorbidity Index ≥ 4 had the lowest cumulative incidence of appropriate therapy. Survival was not different between elderly with Charlson Comorbidity Index 0–1 and youngers. Appropriate therapy rates were not different between those 2 groups. Charlson Comorbidity Index score is helpful to better select elderly candidates for ICD implantation.